PENERAPAN INQUIRY LEARNING BERBANTUAN VIDEO ANIMASI TERHADAP PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Ananda, Fharaz; Rika Perdana, Dayu; Hariyanto, Hariyanto; Syafrudin, Ulwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study was the low learning outcomes in Pancasila Education among fifth-grade students at SDN 5 Metro Timur. This research aimed to determine the effect of the inquiry learning model assisted by animated video media on students’ learning outcomes. The study employed a quasi-experimental design using a nonequivalent control group design. The sample consisted of 41 students selected through purposive sampling. Data were collected through tests and observations and were analyzed using simple linear regression. The results showed that Fcount (16.296) was higher than Ftable (4.38) with a significance value of 0.001, which was lower than 0.05. These findings indicate that the inquiry learning model supported by animated video media has a significant effect on the Pancasila Education learning outcomes of fifth-grade students.